the Development of E-Module IPAS Based on Problem Based Learning Assisted with Articulate Applications to Improve Students Think Critically - Adelweiss Saralee; Yanti Fitria; Elfia Sukma; Abna Hidayati (Postgraduate, University of Mataram, 2024)
Monotonous and boring learning using books and worksheets alone makes students less interested in learning and reduces students' critical thinking abilities. Teachers need to create open materials that are interesting and able to increase students' enthusiasm for learning and improve students' critical thinking skills. This research aims to develop an E-module based on the Problem Based Learning model with various steps in solving problems and containing video and image content that is interesting for students. The research location is SDN 015 Sungai Banyak City. The research subjects were fourth grade elementary school students. This research is R&D development research using the ADDIE model. There are 2 stages of data analysis technique, namely validation carried out by 3 experts. Media experts, language experts and material experts are drawn from expert lecturers and master's graduate teachers. The second stage is practicality taken from fourth grade elementary school students. The research results showed a validity figure of 92.82% in the very valid category and for practicality it was 97.5% for students and 92% for teachers. The obstacles faced are limited time and the need for introduction in creating e-modules using the articulate storyline 3 application.